THE METHODOLOGY OF USING GAME TECHNOLOGIES IN RUSSIAN LANGUAGE LESSONS - Ergasheva Dilfuza Kamilovna (Miasto Przyszłości, 2024)
The article discusses the importance of using gaming technologies in Russian language lessons as one of the powerful teaching tools. The author comes to the conclusion that the use of games in Russian language lessons is recommended when the use of game methods also contributes to the development of a culture of communication and educates an active personality capable of seeing, formulating and solving non-standard problems.